2001
DOI: 10.1046/j.0956-540x.2000.01330.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetotelluric sounding of the Hikurangi Margin, New Zealand

Abstract: Summary Magnetotelluric soundings from 30 sites on the Hikurangi Margin have been used to image the electrical resistivity structure associated with the subduction of the Pacific Plate beneath the Australian Plate along the east coast of the North Island of New Zealand. The data are generally 2‐D in nature and exhibit a strike orientation that is compatible with the observed tectonic strike of the margin. 1‐D inversions of invariant impedance responses from sites on a transect parallel to this orientation yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 41 publications
5
25
0
Order By: Relevance
“…Similar features have been noted in other subduction systems (e.g., Kurtz et al 1986Kurtz et al , 1990Wannamaker et al 1989a, b;Fuji-ta et al 1997). Ingham et al (2001) also reported a perpendicular MT transect ( Fig. 1, AA ) running along the length of the margin, which penetrated into the Wairarapa region at its southern end.…”
Section: Introductionsupporting
confidence: 55%
See 3 more Smart Citations
“…Similar features have been noted in other subduction systems (e.g., Kurtz et al 1986Kurtz et al , 1990Wannamaker et al 1989a, b;Fuji-ta et al 1997). Ingham et al (2001) also reported a perpendicular MT transect ( Fig. 1, AA ) running along the length of the margin, which penetrated into the Wairarapa region at its southern end.…”
Section: Introductionsupporting
confidence: 55%
“…2). Data at 10 of the sites were collected over the summer of 1998/99, while 4 sites were occupied in conjunction with the study reported by Ingham et al (2001). Two of the sites (MGN, KAI) lie to the west of the Wairarapa Fault on the Mesozoic greywacke rocks that make up the main axial ranges of the North Island.…”
Section: Magnetotelluric Datamentioning
confidence: 99%
See 2 more Smart Citations
“…The application of Mohr circles in MT interpretation was introduced by Lilley (1976). Nowadays, this simple technique is used to display the dimensionality of a structure and to infer the regional strike angle (Lilley, 1993(Lilley, , 1998aMakris et al, 1999;Ingham et al, 2001). By simply rotating and then plotting specific rotated components of the measured impedance tensor (e.g.…”
Section: Galvanic Distortion Analysis Of the Ioannina Mt Impedance Esmentioning
confidence: 99%